From hypertrophic cardiomyopathy centers to inherited cardiovascular disease centers in Europe. A small or a major step? A position paper from the Nucleus of the Working Group on Myocardial and Pericardial Diseases of the Portuguese Society of Cardiology - Cardim, Nuno (2011)
The prevalence, complexity, clinical importance, heterogeneity and unpredictability of inherited cardiovascular diseases make the development of inherited cardiovascular disease centers an inevitability, with the ultimate goal of reducing the morbidity and mortality associated with these conditions. An inherited cardiovascular disease center may be seen as a subunit of a cardiology department, with health professionals specializing in these types of disorders, organized to provide excellence in all related areas, including diagnosis, treatment, follow-up, prevention, risk stratification and prognosis. Among its objectives are the development of action protocols and the creation of databases that enable patients to be included in national and international research networks. To achieve these objectives these centers should include functional units of clinical and basic sciences, research, training and education, acting in harmony in a holistic approach to patients and their families. As most experience on inherited cardiovascular diseases is based on hypertrophic cardiomyopathy and on "hypertrophic cardiomyopathy centers", these centers represent an excellent opportunity to learn how to set up inherited cardiovascular disease centers. European centers will differ from country to country, reflecting the heterogeneity of national health systems, but will share a common core, presented in this document. Though we are aware that this ambitious project is not at all easy and may be difficult to implement in its entirety - in fact we consider it a major step - our position is that all the efforts to achieve it are worthwhile, considering that the main goal will always be the well-being of those affected by these particular disorders. © 2011 Sociedade Portuguesa de Cardiologia. Published by Elsevier España, S.L. All rights reserved.